What is the pattern requests for and usage of nasal continuous positive airway pressure (nCPAP) during transport of children younger than 13 years of age, in the Metropolitan area of the Western Cape, South Africa - Du Plessis, Nicole (Division of General Surgery, 2025)
Background: Nasal continuous airway pressure (nCPAP) is used to treat respiratory conditions resulting in respiratory distress. It is a widely accepted method of non-invasive ventilation in children in optimal environments such as the Intensive Care Unit (ICU). It's use outside of ICU settings is increasing, with a consequent increased demand for transfer of children, especially neonates, on nCPAP. Methods: Retrospective data from the Western Cape public sector Emergency Medical Services electronic records (April-June 2019) for cases where a transfer on nCPAP was requested or administered are described. Data described includes patient demographics, facility data, mode of ventilation during transport, and disease profiles. Results: A total of 325 cases were included in the study, of which 289 CPAP requests were made; 226 (78.2%) of these cases were CPAP. It was utilized most in neonates <24 hours old and infants in the 1–3-month age group. Respiratory conditions were the most common reason for needing CPAP (n=181; 76.1%), with pneumonia being documented in 46.4%, and unspecified respiratory distress in 42.5% of cases. Of the 226 CPAP requested and given cases, CPAP was started by the facility in 133 cases (58.8%), with 74.4% of these being district hospitals. Conclusion: nCPAP is the most used form of ventilatory support in children under 13 years during ground interfacility transfers for respiratory conditions. More studies are needed to investigate safety, suitability, and ease of use of CPAP for staff of varying skill sets and whether this makes a difference to outcome.